Behavioural change box? Applying the COM-B model to understand behavioural triggers that support consumption of fruits and vegetable among subscribers of a fruit and vegetable box scheme. Issue 18 (6th December 2021) - Craveiro, Daniela; Marques, Sibila; Bell, Ruth; Khan, Matluba; Godinho, Cristina; Peixeiro, Filomena
Abstract: Objective: To understand the key mechanisms that support healthy dietary habits promoted by fruit and vegetable (F&V) box schemes, testing relevant behaviour change triggers identified under the COM-B model in an evaluation research study of a Portuguese F&V box scheme (PROVE). Design: Correlation study with a post-test-only non-equivalent group design based on survey data. The mechanisms underpinning the differences between subscribers and non-subscribers are operationalised as mediation effects. Data availability, theoretical relevance and empirical validation supported the selection and testing of four potential mediators for the effects of subscribing to the box scheme on F&V consumption. These estimations derive from the coefficients of a structural equation model combined with the product coefficient approach and Sobel test. Setting: The study is part of a wider evaluation study on the impact of the PROVE box scheme on sustainability, health and equity. Participants: A sample of PROVE box subscribers ( n 294) was compared with a matched subsample of non-subscribers ( n 571) in a nationally representative survey. Results: Subscribing to the PROVE box correlates with an increased probability of eating at least five portions of F&V, irrespective of differences in age, education and perceived economic difficulties. Diet quality perceptions, and more robustly, the strength of meal habits and household availability were identified as relevant mediators. Conclusions: The subscription to an F&V box scheme is connected with proximal context that enables the consumption of F&V by ensuring more readily available F&V and better situational conditions associated with healthier meal habits.